Metabolomic Profiling of Brain Protective Effect of Edaravone on Cerebral Ischemia-Reperfusion Injury in Mice - Ma, Hui-fen; Zheng, Fan; Su, Lin-jie; Zhang, Da-wei; Liu, Yi-ning; Li, Fang; Zhang, Yuan-yuan; Gong, Shuai-shuai; Kou, Jun-ping (Frontiers in Pharmacology, 2022)
Edaravone (EDA) injection has been extensively applied in clinic for treating stroke. Nevertheless, the metabolite signatures and underlying mechanisms associated with EDA remain unclear, which deserves further elucidation for improving the accurate usage of EDA. Ischemia stroke was simulated by intraluminal occlusion of the right middle cerebral artery for 1 h followed by reperfusion for 24 h in mice. Brain infarct size, neurogical deficits and lactate dehydrogenase (LDH) level were improved by EDA. Significantly differential metabolites were screened with untargeted metabolomics by cross-comparisons with pre- and post-treatment of EDA under cerebral ischemia/reperfusion (I/R) injury. The possibly involved pathways, such as valine, leucine and isoleucine biosynthesis, phenylalanine metabolism, taurine and hypotaurine metabolism, were enriched with differential metabolites and relevant regulatory enzymes, respectively. The network of differential metabolites was constructed for integral exhibition of metabolic characteristics. Targeted analysis of taurine, an important metabolic marker, was performed for further validating. The level of taurine decreased in MCAO/R group and increased in EDA group. The inhibition of EDA on cerebral endothelial cell apoptosis was confirmed by TdT-mediated dUTP nick-end labeling (TUNEL) stain. Cysteine sulfinic acid decarboxylase (CSAD), the rate-limiting enzyme of taurine generation, significantly increased along with inhibiting endothelial cells apoptosis after treatment of EDA. Thus, CSAD, as the possible new therapeutic target of EDA, was selected and validated by Western blot and immunofluorescence. Together, this study provided the metabolite signatures and identified CSAD as an unrecognized therapeutic intervention for EDA in treatment of ischaemic stroke via inhibiting brain endothelial cells apoptosis.